IDENTIFICATION AND FEATURES OF TREATMENT OF PATIENTS WITH OPEN OCCLUSION IN SPEECH DISORDERS - Nigmatova I.M; Suleymanova D.A; Aralov M.B (Scholar Express Journal, 2024)
In orthodontics of vertical malocclusion, diagnosis and successful treatment of open occlusion have been carried out in many scientific papers, but taking into account the age of the patient, the type of anomaly (true, false) are not specified. Therefore, in our work, we set ourselves the task of diagnosing patients with open occlusion using modern methods, taking into account their age and type of anomaly.
Keywords: Orthodontics; vertical malocclusion